SIMULATION OF FIRE AND EXPLOSION RISK ASSESSMENT MODELING ON CARBON DISULFIDE (CS2) WASTE GAS RECOVERY PLANT ADSORBER TANK - Nasta Ina Robayasa; Tri Yuni Hendrawati; Athiek Sri Redjeki (Faculty of Engineering Universitas Muhammadiyah Jakarta, 2025)
Carbon Disulfide (CS2) is a colorless liquid that is flammable and toxic. In this study, a process safety analysis was conducted at a factory (Carbon Adsorption Plant) with the aim of determining the severity of the impact in the event of a fire, explosion, and environmental pollution or exposure to toxic gases as a result of explosions or system failures from the Adsorber tank in a plant. In this discussion, process safety analysis methods in a plant will be carried out, including QRA (Quantitative Risk Assessment), namely FERA (Fire and Explosion Risk Assessment). The simulation results of the Fire and Explosion modeling on the Adsorber tank (Carbon Adsorption Plant) obtained the fire radiation energy (Radiation Level kW/m2) with the highest value, which is SEP = 46.98 kW/m2. The maximum distance of the fire effect (FireBall) is R = 132.7 m, and the radial range of the fire effect (FireBall) that can cause immediate fatality to humans is Radius = 0 – 24.3 m. The Side-On Blast Overpressure due to the explosion (Bar) has a maximum value of Ps = 19.71 Bar. The maximum distance of the Side-On Blast Overpressure effect is Radius = 324.8 m. The distance range of the explosion effect (Side-On Blast Overpressure) that can cause immediate fatality to humans and potential fatal damage to assets/buildings (Damage Rupture) is Radius = 219.3 – 349.2 m with Ps = 0.5 – 19.71 Bar. The concentration of toxic gas and the exposure distance of toxic gas from CS2 gas (Dose Concentration and Distance) have a maximum value of C = 984,201.2 ppm. The range of the radius from the effects of Fire, Explosion and Toxic Gas Exposure (Toxic Gas Dispersion) that safe for operations activity is Radius > 611.9 m (west side) and > 99.5 m (east side).